Tyrosinemia II in two siblings. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
Case 1. First born from 1st degree cousin parents. At 2 months keratoconjunctivitis healed without residua after 10 months. At the age of 2 years onset of punctate palmoplantar keratoderma with multiple foci (Fig. 1). The lesions recurred periodically, started dot-like and progressively enlarged, improved with summer and were very painful, so that the little boy crawled to move. The histological examination showed hyperkeratosis and elongated epidermal crests (Fig. 2). In spite of the various treatments, included rX therapy, the lesions continuously recurred and improved only with etretinate 1mg/kg per day. At the age of 3 appeared emotional instability. At the age of 16 the analysis of urine amino acids led to diagnose tyrosinemia II and to start a diet with low content of phenylalanine and tyrosine. Case 2. Younger sister of case 1 with similar symptoms and signs. Keratoderma started earlier than in his brother, but she had not psychological problems. The diet led to complete regression of the skin lesions. At the age of 18 transplantation of the left cornea.